Audience Participation in Interactive Art Systems: Is Instructional Signage a Necessary Evil? - Cordeiro, João; Martins de Abreu, F.; Estadieu, Gerald (Proceedings of the 8th International Conference on Digital Arts, 2017)
2 citations (Crossref) [2022-10-27]

3D Printing Objects As Installation Art: Standing Humanity: 3D Yan Character - Estadieu, Gérald; Martins de Abreu, F.; Barbosa, Álvaro (Proceedings of the 8th International Conference on Digital Arts (ARTECH 217), 2017)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

Creative Engagement: Multimodal digital games in children's learning environment in Macau S.A.R. - Martins de Abreu, F.; Barbosa, Álvaro (Proceedings of the 8th International Conference on Digital Arts, 2017)
One of the biggest challenges that we have encountered, when trying to encourage digital games in schools, is trying to explain what its benefits are in teaching and learning environments. In this pilot experimental study we explore how multimodal audio and visual games can be used in learning environments for children, specifically by fostering creative behaviors through User-Centered design approaches. To achieve this objective, a framework is being developed with multimodal experiences based on flexible design patterns that exploits basic visual and audio elements, allowing children from three to six years of age to play and learn through fun and subsequently trigger creative behaviors. These studies are making use of tangible objects, digital games and mobile platforms. We are making use of commercial digital games to understand and discuss the affordances of these games in an educational environment and how they support creativity in learning. (Fig.1)
Keywords: Children; Creative Learning; Devices; Digital Games; Mobile; Multimodal; Tangible Technologies; User-Centered Design

The impact of multimodal digital games in children’s learning environments - Martins de Abreu, F.; Barbosa, Alvaro (2017)